The Implementation of Islamic Law and Cultural Norms in the Socio-Political Landscape of Indonesia - Ridhwan, Muhammad; Widiastuti, Ika; Azkia Muhammad Adiba, Mirza (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This article examines the intricate relationship between Islam, politics, and culture in influencing daily life in many regions of Indonesia, under the overarching context of the nation-state. It classifies the relationship between Islam and the state under three paradigms: interplanetary, secular, and symbiotic. These paradigms exhibit variation between provinces, illustrating distinct historical, political, and cultural circumstances. The Indonesian constitution technically enforces Islamic law alone in Aceh, although three principal orientations of Islamic law are present throughout the nation: Islam as a political philosophy, as a moral-ethical framework, and a moderate model that integrates formal implementation with ethical influence beyond state legislation. The research utilizes a qualitative, literature-based approach, integrating information from academic publications, journals, and historical documents. It indicates that differences in daily Islamic practices are influenced by regional histories, colonial legacies, local governance, and socio-political dynamics. These circumstances impede the establishment of a cohesive Islamic identity throughout Indonesia, a predominantly Muslim nation. The research highlights that the connection between Islam and the state in Indonesia is dynamic and adapts to changing political and societal conditions.